2009
DOI: 10.1186/1756-6606-2-22
|View full text |Cite
|
Sign up to set email alerts
|

A systematic investigation of the protein kinases involved in NMDA receptor-dependent LTD: evidence for a role of GSK-3 but not other serine/threonine kinases

Abstract: Background: The signalling mechanisms involved in the induction of N-methyl-D-aspartate (NMDA) receptor-dependent long-term depression (LTD) in the hippocampus are poorly understood. Numerous studies have presented evidence both for and against a variety of second messengers systems being involved in LTD induction. Here we provide the first systematic investigation of the involvement of serine/threonine (ser/thr) protein kinases in NMDAR-LTD, using whole-cell recordings from CA1 pyramidal neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 58 publications
4
76
2
1
Order By: Relevance
“…However, LTD does not require phosphorylation of Ago2 at S387, which is in agreement with a previous study demonstrating that LTD is normal in hippocampal slices from LIMK1 knockout mice (Meng et al , 2002). Furthermore, a previous report suggested that Akt activity is not required for the expression of CA3‐CA1 LTD (Peineau et al , 2009), which is consistent with our observation that Ago2 S387 mutants have no effect on CA3‐CA1 LTD.…”
Section: Discussionsupporting
confidence: 93%
“…However, LTD does not require phosphorylation of Ago2 at S387, which is in agreement with a previous study demonstrating that LTD is normal in hippocampal slices from LIMK1 knockout mice (Meng et al , 2002). Furthermore, a previous report suggested that Akt activity is not required for the expression of CA3‐CA1 LTD (Peineau et al , 2009), which is consistent with our observation that Ago2 S387 mutants have no effect on CA3‐CA1 LTD.…”
Section: Discussionsupporting
confidence: 93%
“…Some, but not all, reports showed that inhibitors of p38 block LTD induction in the CA1, suggesting that GRF1 activation of p38 could be involved in this process as well (2,(25)(26)(27). However, stimuli that activate LTD did not lead to p38 activation (data not shown).…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, PKA activation leads to the phosphorylation and activation of the cAMP response element binding protein (CREB), which is required for activity-dependent gene transcription during the late phase of postsynaptic LTP and controls neuronal excitability (for a review, see [45]), two mechanisms which could also contribute to the behavioural deficits observed in Ophn1-deficient mice. In addition, PKA signalling is involved in hippocampal LTD [46,47]. However, because dihydroxyphenylglycine (DHPG)-induced LTD is normal in Ophn1 2/y mice [9], it is unlikely that a deficit in hippocampal NMDAR-dependent LTD plays a major role in the impairment of contextual fear memory.…”
Section: Discussionmentioning
confidence: 99%